Kebijakan Rezim Taliban terhadap Perempuan Afghanistan dalam Perspektif Etika dan Hukum Internasional - Syakira Nazla Rifat Junaedi (Media Hukum Indonesia (MHI), 2026)
This study aims to analyze the Taliban regime's policies toward Afghan women from the perspectives of ethics and international law. The research employs a normative legal method using statutory, conceptual, and case approaches. The findings show that Taliban policies restricting women's access to education, employment, freedom of movement, and public participation are inconsistent with ethical theories, particularly social morality, virtue ethics, utilitarianism, and deontology. Furthermore, these policies are contrary to international legal standards, especially the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), which Afghanistan has ratified. Therefore, the Taliban's policies toward Afghan women may be regarded as a form of discrimination that violates the principles of equality, non-discrimination, and human rights protection.